STUDY EFFECT OF ADDING ZEOLITE AND BANANA STEM ON THE QUALITY OF ORGANIC FERTILIZER FROM CHICKEN MANURE - sri wardhani; Darjito Darjito; Nurul Indahsari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2016)
The purpose of this study was to determine the character of a zeolite, knowing the ratio of the addition of zeolites and zeolite activation on levels of N from organic fertilizers, determine the effect of banana stems against K content of manure and know the quality of the organic fertilizer produced. Research has been done that is activated zeolite with HCl 0.4 m. Natural zeolites and activated zeolite characterization has been done using XRF, AAS and SAA. Organic fertilizer production is done by adding the zeolite and the banana stems in 500 grams of chicken manure with the addition of zeolite variation by 5, 10, 15, 20 and 25 grams. The addition of banana stem variations of 100, 150, 200 and 250 grams. Organic fertilizer analysis contains N, P, and K. The results showed that the zeolite contains elements Si, Al, Ca and Fe. AAS results showed that the zeolites contain elements K of 0.258% and 0.405% respectively for natural zeolites and zeolite activation. SAA results showed that the zeolite is a mesoporous material with a surface area, pore diameter and volume respectively was 244.2 m2 / g, 6.008 nm, 0.099 mL / g for natural zeolites and zeolite activation was 251.7 m2 / g, 6.046 nm and 0,088mL / g. The addition of zeolite can increase the levels of N fertilizer. The addition of zeolite activation in the manufacture of manure increases the levels of N and K but lower levels of P. The addition of a banana tree in the manufacture of organic fertilizer can increase the levels of N, P and K fertilizer. Increasing the ratio of banana stems not affect the K value of manure produced. Quality of the manure generated from livestock manure to 500 grams, 250 grams and 25 grams of banana stem zeolite activation had higher levels of N 4.90%, 1.08% P2O5, K2O 0.62%, 9.31% water content, organic-C 33.48% and C / N ratio of 6.83%.